PENGARUH PENGALAMAN AUDIT, KOMITMEN PROFESIONAL, ORIENTASI ETIKA DAN NILAI ETIKA ORGANISASI TERHADAP PENGAMBILAN KEPUTUSAN ETIS AUDITOR INTERNAL DI KOTA PALEMBANG - Emilia Gustini (Jurnal Ilmiah Ekonomi Global Masa Kini)
The objective of this study is to reveal the partial influence of audit experience, professional commitment, ethical orientation and ethical value of organization on the ethical decision making of the internal auditors in the city of Palembang and the simultaneous influence of audit experience, professional commitment, ethical orientation and ethical value of organization to the ethical decision making of the internal auditors in the city of Palembang. The operational variables of the study are audit experience, professional commitment, ethical orientation and ethical value of  organization and ethical decision making of the internal auditors. The population of the study consists of internal auditors working at the companies in the city of Palembang. The result of the study on the internal auditor in the city of Palembang reveals that the variable ethical value of  organization partially  have a significant influence to the ethical  decision making of the internal auditors , while the variables of audit experience, professional commitment, ethical orientation do not have a significant influence to the ethical  decision making of the internal auditors. Simultaneously, the variabels of audit experience, professional commitment, ethical orientation and ethical value of organization have asignificant influence to the ethical  decision making of the internal auditors with the result of  F-count bigger than F-table (9.536>2.796). Key words : audit experience, professional commitment, ethical orientation and ethical value of organization, ethical decision making.